2019
DOI: 10.3390/catal9030293
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal Phosphides for the Catalytic Hydrodeoxygenation of Waste Oils into Green Diesel

Abstract: Recently, catalysts based on transition metal phosphides (TMPs) have attracted increasing interest for their use in hydrodeoxygenation (HDO) processes destined to synthesize biofuels (green or renewable diesel) from waste vegetable oils and fats (known as hydrotreated vegetable oils (HVO)), or from bio-oils. This fossil-free diesel product is produced completely from renewable raw materials with exceptional quality. These efficient HDO catalysts present electronic properties similar to noble metals, are cost-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(29 citation statements)
references
References 129 publications
1
28
0
Order By: Relevance
“…Moreover, Co-and Nipromoted MoS 2 catalyst was also used to co-process diesel and vegetable oil via hydrodeoxygenation reaction [226]. Alvarez-Galvan et al [227] demonstrated that transition metals phosphides were useful as a hydrodeoxygenation catalyst for waste cooking oil to green biodiesel. More research work is required to explore the possibility of TMDC materials in this field.…”
Section: Fuel Hydrodeoxygenationmentioning
confidence: 99%
“…Moreover, Co-and Nipromoted MoS 2 catalyst was also used to co-process diesel and vegetable oil via hydrodeoxygenation reaction [226]. Alvarez-Galvan et al [227] demonstrated that transition metals phosphides were useful as a hydrodeoxygenation catalyst for waste cooking oil to green biodiesel. More research work is required to explore the possibility of TMDC materials in this field.…”
Section: Fuel Hydrodeoxygenationmentioning
confidence: 99%
“…In contrast, the use of metal–non‐metal nanoalloys, such as metal phosphide nanoalloy catalysts, has not been studied comprehensively. Few innovative metal phosphide catalysts have been reported in organic synthesis [19–24] despite their high catalytic potential as hydrotreating catalysts, as well as electrocatalysts and photocatalysts for energy conversion [25–31] . In this context, our research group has recently focused on exploring novel catalysis by metal phosphide nanoalloys.…”
Section: Introductionmentioning
confidence: 99%
“…The mild acidity of the catalysts promotes the generation of many side reactions, as a result, coking of the catalyst may occur. Further reasons for the loss of catalytic activity may be sintering, poisoning or active metal leaching which reduces the number of active sites [17]. Kubička and Horáček [18] investigated the reasons for deactivation of hydrodesulphurization (HDS) catalysts during the deoxygenation of vegetable oils.…”
Section: Introductionmentioning
confidence: 99%